Progress in the Developments of Heat Transfer, Nanoparticles in Fluid, and Automotive Radiators: Review and Computational Bibliometric Analysis - Asep Bayu Dani Nandiyanto; Dwi Novia Al Husaeni; Abdulkareem Sh. Mahdi Al Obaidi; Belkheir Hammouti (Automotive Experiences, 2024)
This research aims to determine the development of the number of scientific publications in the field of particulate matter; the number of publications from each country that publish articles on heat transfer, nanoparticles, and automotive radiators; articles with the highest number of citations; and visualization publication development map based on keywords. To achieve this goal, quantitative descriptive research was carried out using bibliometric analysis with the help of the publish or perish (PoP) application to collect data and VOSviewer to visualize related research topics. The article data taken is limited to 2018-2023. In addition, the terms heat transfer, nanoparticles, and automotive radiators are used as keywords in collecting article data using the pop application. Research on heat transfer, nanoparticles, and automotive radiators has increased in 2020 and India has become one of the countries that has contributed many publications on this topic. From the mapping results, research on heat transfer, nanoparticles, and automotive radiators is still being carried out frequently, especially in early 2020-2021. This research can help academics determine which problems to research and can be used as a reference for further research.